Continuous thermosalinograph oceanography along RV MARIA S. MERIAN cruise track MSM112/2 - Frank Nitsche; Michael Schlundt (PANGAEA, 2023)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems. Usually, the systems are changed after 12 hours (during the first week of the cruise only MC1 was used). While temperature is taken at the water inlet in about 6.5 m depth, salinity is estimated within the interior measurement container from conductivity and interior temperature. No temperature and salinity calibration were performed. For details to all processing steps see Data Processing Report.